Proud to be me developing self-esteem - Grant, Sandra Carr (The Center [production company], 1978)
A combination of interviews and dramatic scenarios on the life of students. It shows strategies for setting realistic goals, skills for controlling the way they feel about themselves and evaluate their strengths and weaknesses.